Flexible ceramic nanofiber membrane as well as preparation method and application thereof

The flexible ceramic nanofiber membrane was prepared by sol-gel method and electrospinning technology, which solved the problem of low output voltage of existing hydrovoltaic devices, achieved efficient water-induced power generation, and obtained high output voltage and good stability.

CN119507116APending Publication Date: 2025-02-25ZHEJIANG SCI-TECH UNIV

Patent Information

Application Number
CN202411668911.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The output voltage of existing nanofiber-based hydrovoltaic devices is low, which is much lower than that of other energy conversion devices, and there is a performance bottleneck.

Method used

Flexible ceramic nanofiber membranes are prepared by sol-gel method and electrospinning technology to improve the porosity of ceramic nanofibers and form a composite pore structure with mesoporous and macropores coexisting.

Benefits of technology

It significantly enhances the water-induced power generation capacity, obtains a high output voltage, and the flexible ceramic nanofiber membrane has good flexibility and stability, and can continuously generate electricity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507116A_ABST
    Figure CN119507116A_ABST
Patent Text Reader

Abstract

The invention provides a flexible ceramic nanofiber membrane as well as a preparation method and application thereof. The preparation method comprises the following steps: adding polyvinyl alcohol into water, and heating and stirring in a water bath kettle until the polyvinyl alcohol is completely dissolved to obtain a polyvinyl alcohol solution; stirring the precursor material, an acid catalyst and water until hydrolysis to obtain oxide substrate sol; mixing a polyvinyl alcohol solution with the oxide substrate sol, adding a pore forming agent, uniformly mixing, and performing electrostatic spinning to obtain a precursor composite nanofiber membrane; and calcining the precursor composite nanofiber membrane at high temperature to obtain the flexible ceramic nanofiber membrane. According to the prepared flexible ceramic nanofiber membrane, fibers are in a shape similar to sugarcoated haws on sticks, the porosity is high, based on the charge property of the flexible ceramic nanofiber membrane, in the water-induced power generation process, counter ions are generated on the solid-liquid contact surface in an electrolyte aqueous solution and a ceramic fiber channel, and the water-induced power generation efficiency is improved. Good flexibility and stability are shown through flowing potential driving, continuous power generation can be achieved, and high output voltage is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water-induced power generation devices, and in particular to a flexible ceramic nanofiber membrane and a preparation method and application thereof. Background Art

[0002] With the continuous development of social economy and the rapid growth of global population, people's demand for energy is also increasing. In order to meet this challenge, the country has put forward the goals of "carbon peak" and "carbon neutrality" to promote the sustainable development of economy, environment and energy. To achieve this goal, the development and utilization of clean energy has become a strategic choice at present.

[0003] In nature, water covers 71% of the Earth's surface. Hydropower generation technology has a long history. However, most existing technologies rely mainly on the gravity and kinetic energy of liquid water to generate electricity. These systems are inherently incompatible with the development of self-powered devices. The ideal efficient energy conversion method should be naturally driven, such as through the evaporation process of water. Water absorbs heat from the environment to form water vapor, and this process does not require external mechanical energy input. The technology of using the natural evaporation of water to generate electricity is called water-induced power generation, which is a green and environmentally friendly innovative power generation technology. When water molecules come into contact with the solid surface, due to the action of the solid surface charge, the anions / cations in the water will be adsorbed to the solid surface and form a charged area on the solid surface, resulting in the separation of the parts with different charges in the water, thereby forming a double electric layer structure near the contact surface of the two phases.

[0004] In recent years, research on surface nanomaterials has shown that they can couple with various liquids and generate electricity. Therefore, the rapid development of nanomaterials has made it possible to extract electricity from water, which in turn has promoted the development of automated electricity. Electrospun nanofibers have the advantages of high specific surface area and high porosity. The formed nanofiber membrane has numerous micro-nano channels. There are two power generation mechanisms at the same time. One is the current generated by ion diffusion driven by concentration gradient, and the other is the current caused by the flow of liquid on the charged surface in the solid channel. When the lower end of the electrospun nanofiber membrane is immersed in water, the high porosity of the membrane prompts water to spontaneously penetrate upward along the pores of the fiber membrane through capillary force. In this process, the absorption of water is not only affected by the porous structure and hydrophilicity of the membrane, but also related to the pore size, pore size distribution and surface chemical properties of the fiber. As the water content gradually rises, the movement of charged particles in the solution will become more obvious. However, the output voltage of existing nanofiber-based hydrovoltaic devices is mostly only a few hundred millivolts, which is much lower than other energy conversion devices, so there is still a need to further break through the existing performance bottleneck. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the shortcomings of the prior art, the present invention provides a flexible ceramic nanofiber membrane and a preparation method and application thereof. The ceramic nanofiber membrane prepared by the sol-gel method and electrospinning technology has natural charge characteristics, improves the porosity of ceramic nanofibers, effectively enhances the water-induced power generation capacity, and solves the problems raised in the above-mentioned background technology.

[0007] (II) Technical solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] According to a first aspect of the present invention, there is provided a method for preparing a flexible ceramic nanofiber membrane, comprising the following steps:

[0010] S1. Add polyvinyl alcohol to water, heat and stir in a water bath until completely dissolved to obtain a polyvinyl alcohol solution;

[0011] S2, stirring the precursor material, the acid catalyst and water until hydrolysis occurs to obtain an oxide-based sol;

[0012] S3, mixing the polyvinyl alcohol solution and the oxide substrate sol, adding a pore-forming agent, mixing evenly, and obtaining a precursor composite nanofiber membrane by electrospinning;

[0013] S4, calcining the precursor composite nanofiber membrane at high temperature to obtain the flexible ceramic nanofiber membrane.

[0014] Preferably, in step S1, the mass fraction of the polyvinyl alcohol solution is 6 to 20 wt %;

[0015] The water bath heating temperature is 70-95°C.

[0016] Preferably, in step S2, the precursor material is selected from at least one of sodium silicate, calcium silicate, tetraethyl silicate, zirconium oxychloride, and zirconium nitrate;

[0017] The acid catalyst is selected from at least one of phosphoric acid, acetic acid or hydrochloric acid;

[0018] The mass fraction of the precursor material in the oxide-based sol is 25 to 75 wt %;

[0019] The mass fraction of the acid catalyst in the oxide-based sol is 0.01 to 1.0 wt %;

[0020] The hydrolysis time is 2 to 5 hours.

[0021] Preferably, in step S3, the mass ratio of the polyvinyl alcohol solution to the oxide base sol is 1:1-2;

[0022] The mass ratio of the oxide base sol to the pore-forming agent is 1:0.001-1;

[0023] The pore-forming agent is selected from polymer nano-microspheres with a thermal decomposition temperature of ≤550°C.

[0024] Preferably, the pore-forming agent is selected from at least one of polyacrylamide nanospheres, polystyrene nanospheres, polylactic acid nanospheres, polymethyl methacrylate nanospheres, and polyacrylic acid nanospheres;

[0025] The particle size of the pore-forming agent is 20 to 1000 nm.

[0026] Preferably, in step S3, the electrostatic voltage of the electrospinning is 20 to 30 kV, and the spinning speed of the electrospinning is 0.8 to 1.3 mL / h;

[0027] The electrospinning device is selected from any one of a single-needle type, a multi-needle type, a needle-free type or an electrostatic direct writing type.

[0028] Preferably, in step S4, the high temperature calcination conditions are: in an air atmosphere, heating to 650-1000° C. at a rate of 1-10° C. / min, and keeping the temperature for 0.5-5 h.

[0029] According to the second aspect of the present invention, a flexible ceramic nanofiber membrane obtained based on the above-mentioned preparation method is provided, the fibers of the flexible ceramic nanofiber membrane are in the shape of candied haws, and the interior of the fibers of the flexible ceramic nanofiber membrane is a composite pore structure with coexistence of mesopores and macropores.

[0030] According to a third aspect of the present invention, there is provided an application of a flexible ceramic nanofiber membrane in a water-induced power generation device, wherein one end of the flexible nanofiber membrane is immersed in an electrolyte solution to form the water-induced power generation device.

[0031] Preferably, the electrolyte solution is selected from water or an inorganic salt aqueous solution;

[0032] The pH of the electrolyte solution is 0-7.

[0033] (III) Beneficial effects

[0034] The present invention provides a flexible ceramic nanofiber membrane and a preparation method and application thereof.

[0035] Beneficial effects:

[0036] (1) This scheme provides a method for preparing a flexible ceramic nanofiber membrane. With the help of a pore-forming agent, a sol-gel, electrospinning and high-temperature calcination process is combined to prepare a flexible ceramic nanofiber membrane having a candied haws-like shape, forming a composite pore structure with coexistence of mesopores and macropores inside the fiber. The preparation method is simple and easy to operate.

[0037] (2) Compared with the existing fiber-based hydrovoltaic devices, the flexible ceramic nanofiber membrane provided in this scheme is shaped like a candied haws, is resistant to high temperatures, has stable chemical properties, and has a high porosity. In addition, based on its own charge properties, it produces counter ions on the surface of solid-liquid contact between the electrolyte aqueous solution and the ceramic nanofiber channel. The migration of ions with the evaporation of water forms an ion concentration difference. Driven by the flow potential, it exhibits good flexibility and stability, can generate electricity continuously, and obtain a higher output voltage. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a flow chart of a method for preparing a water-induced power generation device based on a flexible ceramic nanofiber membrane according to the present invention;

[0039] Figure 2 The surface and cross-sectional scanning electron microscope images of the flexible ceramic nanofiber membrane prepared in Example 1 of the present invention, wherein (a) is a surface schematic diagram and (b) is a cross-sectional schematic diagram;

[0040] Figure 3 This is a comparison diagram of the power generation performance induced by the flexible ceramic nanofiber membrane prepared in Example 1 of the present invention at different pH values;

[0041] Figure 4 Characterization of the softness of the flexible ceramic nanofiber membrane prepared in Example 2 of the present invention;

[0042] Figure 5 This is a comparison chart of the induced power generation performance of water induction devices with different numbers of series connections provided in Example 2 of the present invention. DETAILED DESCRIPTION

[0043] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Since there are many types of oxide ceramic fibers, such as silica aluminum fiber, zirconium dioxide fiber, titanium dioxide fiber, aluminum oxide fiber, silicon dioxide fiber, etc., all have good chemical stability and mechanical properties, the ceramic nanofiber membrane obtained by combining the sol-gel method and the scenic spinning technology in the present invention has an electric charge. In order to increase the porosity of the ceramic nanofiber, the present invention provides a method for preparing a flexible ceramic nanofiber membrane, comprising the following steps:

[0045] S1. Add polyvinyl alcohol to water, heat and stir in a water bath until completely dissolved to obtain a polyvinyl alcohol solution;

[0046] S2, stirring the precursor material, the acid catalyst and water until hydrolysis occurs to obtain an oxide-based sol;

[0047] S3, mixing the polyvinyl alcohol solution and the oxide substrate sol, adding a pore-forming agent, mixing evenly, and obtaining a precursor composite nanofiber membrane by electrospinning;

[0048] S4. The precursor composite nanofiber membrane is calcined at high temperature to obtain a flexible ceramic nanofiber membrane.

[0049] In a specific embodiment, in step S1, the mass fraction of the polyvinyl alcohol solution is 6 to 20 wt %. Optionally, the mass fraction of the polyvinyl alcohol solution is selected from any value of 6 wt %, 8 wt %, 10 wt %, 14 wt %, 16 wt %, 20 wt % or a range between any two values;

[0050] The temperature of the water bath heating is 70-95°C. Optionally, the temperature of the water bath heating is selected from any value among 70°C, 75°C, 80°C, 85°C, 90°C or a range value between any ratios.

[0051] The polyvinyl alcohol solution is used as the matrix of the fiber. By controlling the temperature of the water bath heating and the mass fraction of the polyvinyl alcohol solution, the fiber membrane after spinning can have a stable structure.

[0052] In step S2, the precursor material reacts with the acid catalyst in water to generate an oxide-based sol. The acid catalyst promotes the hydrolysis and condensation of the precursor material to form a controllable sol base, providing a basis for subsequent ceramicization.

[0053] In a specific embodiment, in step S2, the precursor material is selected from at least one of sodium silicate, calcium silicate, tetraethyl silicate, zirconium oxychloride, and zirconium nitrate;

[0054] The acid catalyst is selected from at least one of phosphoric acid, acetic acid or hydrochloric acid;

[0055] The mass fraction of the precursor material in the oxide substrate sol is 25 to 75 wt %;

[0056] The mass fraction of the acid catalyst in the oxide-based sol is 0.01 to 1.0 wt %;

[0057] The hydrolysis time is 2 to 5 hours.

[0058] In step S3, the two solutions are mixed and then a pore-forming agent is added to form a precursor composite nanofiber membrane by electrostatic spinning. During the electrostatic spinning process, the fibers are formed and the pore-forming agent is dispersed in the fibers, providing conditions for the subsequent formation of a porous structure.

[0059] In a specific embodiment, in step S3, the mass ratio of the polyvinyl alcohol solution to the oxide base sol is 1:1-2;

[0060] The mass ratio of the oxide base sol to the pore-forming agent is 1:0.001-1;

[0061] The pore-forming agent is selected from polymer nanospheres with a thermal decomposition temperature of ≤550°C. Optionally, the pore-forming agent is selected from at least one of polyacrylamide nanospheres, polystyrene nanospheres, polylactic acid nanospheres, polymethyl methacrylate nanospheres, and polyacrylic acid nanospheres.

[0062] The particle size of the pore-forming agent is 20 to 1000 nm.

[0063] In the electrospinning process, the mixed solution containing the pore-forming agent, polyvinyl alcohol and oxide substrate sol is immediately electrospun. By applying voltage, the spinning solution generates a continuous jet and is fully stretched. The water solvent evaporates in this process, and the jet undergoes phase separation and solidifies to form a precursor composite nanofiber membrane.

[0064] Specifically, the electrostatic voltage is 20-30 kV, and the electrospinning speed is 0.8-1.3 mL / h;

[0065] The electrospinning device is selected from any one of a single-needle type, a multi-needle type, a needle-free type or an electrostatic direct writing type.

[0066] In step S4, the prepared precursor composite nanofiber membrane is calcined at high temperature to remove the pore-forming agent, leaving a stable ceramic skeleton, while giving the fiber membrane excellent chemical stability and mechanical properties. In addition, during the high-temperature calcination process, a porous structure is formed, which greatly increases the specific surface area and porosity.

[0067] In a specific embodiment, the high temperature calcination conditions are: in an air atmosphere, the temperature is raised to 650-1000° C. at a rate of 1-10° C. / min, and kept at this temperature for 0.5-5 h.

[0068] The prepared flexible ceramic nanofiber membrane is applied to a water-induced power generation device. Specifically, one end of the flexible nanofiber membrane is immersed in an electrolyte solution. Since the oxide colloidal particles in the flexible ceramic nanofiber membrane have negative charges, when one end of the flexible ceramic nanofiber membrane contacts the electrolyte solution, it will adsorb cations in the electrolyte solution, and the anions will gather at the end immersed in the electrolyte solution. The cations are attracted to the surface to form an overlapping double-layer structure, and finally the positive charges move in a directional manner under a continuous pressure gradient, forming a stable flow potential. The water-induced power generation device in the present invention can be connected into multiple power generation units in series or in parallel.

[0069] In a specific embodiment, the electrolyte solution is selected from water or an aqueous solution of an inorganic salt;

[0070] The pH of the electrolyte solution is 0-7.

[0071] The technical solution of the present invention is described in detail below in conjunction with specific embodiments.

[0072] Example 1

[0073] A method for preparing a water-induced power generation device based on a flexible ceramic nanofiber membrane, the process flow is as follows Figure 1 As shown;

[0074] Step 1, add 3 g of polyvinyl alcohol to 27 g of deionized water, heat to 80° C. in a water bath and stir evenly to obtain a polyvinyl alcohol solution;

[0075] Step 2, adding 8.33 g of tetraethyl silicate to 7.2 g of deionized water, and then adding 0.039 g of boric acid to adjust the pH, stirring for 270 min until hydrolysis, to obtain an oxide-based sol;

[0076] Step 3, 10g of polyvinyl alcohol solution and 10g of oxide substrate sol are mixed, and then 2.4g of polystyrene nanospheres with a particle size of 300nm are added, and the mixture is stirred for 210min to obtain a precursor solution containing polyvinyl alcohol / SiO2 / PS, and the precursor solution is subjected to electrostatic spinning, the electrostatic voltage is 20kV, the spinning rate is 0.8mL / h, the distance from the spinneret to the roller mobile device is 15cm, the spinning time is 12.5h, and a precursor composite nanofiber membrane is obtained after the spinning is completed;

[0077] Step 4: Place the precursor composite nanofiber membrane in a muffle furnace, heat it to 800°C at a rate of 5°C / min in an air atmosphere, and naturally cool it to room temperature after 30 minutes to obtain a flexible ceramic nanofiber membrane. The surface and cross-sectional scanning electron microscopy images of the flexible ceramic nanofiber membrane are as follows: Figure 2 As shown, it can be seen that the fibers in the flexible ceramic nanofiber membrane are in the shape of candied haws;

[0078] Step 5. Add 0.5 g of sodium chloride powder into 20 mL of deionized water and continue stirring until the sodium chloride is completely dissolved to form the electrolyte solution in the water-induced power generation device; cut the flexible ceramic nanofiber membrane into a 2 cm × 1 cm rectangle, immerse its bottom in the electrolyte solution, and build a water-induced power generation device.

[0079] Clamp the Keithley2400 on both sides of the flexible ceramic nanofiber membrane, record the voltage after the screen reading is completely stable, and then adjust the pH of the electrolyte solution with boric acid. After the adjusted pH values ​​are 1, 3, 5, and 7, the voltage test results of water-induced power generation are as follows: Figure 3 As shown. Figure 3 It can be seen that as the pH in the electrolyte solution gradually increases, the voltage decreases.

[0080] Example 2

[0081] A method for preparing a water-induced power generation device based on a flexible ceramic nanofiber membrane comprises the following steps:

[0082] Step 1, add 3 g of polyvinyl alcohol to 27 g of deionized water, heat to 80° C. in a water bath and stir evenly to obtain a polyvinyl alcohol solution;

[0083] Step 2, adding 8.33 g of tetraethyl silicate to 7.2 g of deionized water, and then adding 0.039 g of boric acid to adjust the pH, stirring for 270 min until hydrolysis, to obtain an oxide-based sol;

[0084] Step 3, 10g of polyvinyl alcohol solution and 10g of oxide substrate sol are mixed, and then 0.48g of polystyrene nanospheres with a particle size of 300nm are added, and the mixture is stirred for 210min to obtain a precursor solution containing polyvinyl alcohol / SiO2 / PS, and the precursor solution is subjected to electrostatic spinning, the electrostatic voltage is 20kV, the spinning rate is 0.8mL / h, the distance from the spinneret to the roller mobile device is 15cm, the spinning time is 12.5h, and a precursor composite nanofiber membrane is obtained after the spinning is completed;

[0085] Step 4: Place the precursor composite nanofiber membrane in a muffle furnace, heat it to 650°C at a rate of 5°C / min in an air atmosphere, and naturally cool it to room temperature after 30 minutes to obtain a flexible ceramic nanofiber membrane. The flexibility test of the flexible ceramic nanofiber membrane is as follows: Figure 4 As shown, it can be seen that the flexible ceramic nanofiber membrane can be folded and curled, and has excellent flexibility;

[0086] Step 5. Add 0.5 g of sodium chloride powder into 20 mL of deionized water and continue stirring until the sodium chloride is completely dissolved to form the electrolyte solution in the water-induced power generation device; cut the flexible ceramic nanofiber membrane into a 2 cm × 1 cm rectangle, immerse its bottom in the electrolyte solution, and build a water-induced power generation device.

[0087] Clamp the Keithley2400 on both sides of the flexible ceramic nanofiber membrane, and record the voltage after the screen reading is completely stable. Figure 5 The voltage values ​​of flexible ceramic nanofiber membranes with different numbers of series connections were measured. It can be seen that the voltage increases as the number of series connections increases.

[0088] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a flexible ceramic nanofiber membrane, characterized in that: The following steps are involved: S1. Add polyvinyl alcohol to water, heat and stir in a water bath until completely dissolved to obtain a polyvinyl alcohol solution; S2, stirring the precursor material, the acid catalyst and water until hydrolysis occurs to obtain an oxide-based sol; S3, mixing the polyvinyl alcohol solution and the oxide substrate sol, adding a pore-forming agent, mixing evenly, and obtaining a precursor composite nanofiber membrane by electrospinning; S4, calcining the precursor composite nanofiber membrane at high temperature to obtain the flexible ceramic nanofiber membrane.

2. The method for preparing a flexible ceramic nanofiber membrane according to claim 1, characterized in that: In step S1, the mass fraction of the polyvinyl alcohol solution is 6 to 20 wt %; The water bath heating temperature is 70-95°C.

3. The method for preparing a flexible ceramic nanofiber membrane according to claim 1, characterized in that: In step S2, the precursor material is selected from at least one of sodium silicate, calcium silicate, tetraethyl silicate, zirconium oxychloride, and zirconium nitrate; The acid catalyst is selected from at least one of phosphoric acid, acetic acid or hydrochloric acid; The mass fraction of the precursor material in the oxide-based sol is 25 to 75 wt %; The mass fraction of the acid catalyst in the oxide-based sol is 0.01 to 1.0 wt %; The hydrolysis time is 2 to 5 hours.

4. The method for preparing a flexible ceramic nanofiber membrane according to claim 1, characterized in that: In step S3, the mass ratio of the polyvinyl alcohol solution to the oxide base sol is 1:1-2; The mass ratio of the oxide base sol to the pore-forming agent is 1:0.001-1; The pore-forming agent is selected from polymer nano-microspheres with a thermal decomposition temperature of ≤550°C.

5. The method for preparing a flexible ceramic nanofiber membrane according to claim 4, characterized in that: The pore-forming agent is selected from at least one of polyacrylamide nanospheres, polystyrene nanospheres, polylactic acid nanospheres, polymethyl methacrylate nanospheres, and polyacrylic acid nanospheres; The particle size of the pore-forming agent is 20 to 1000 nm.

6. The method for preparing a flexible ceramic nanofiber membrane according to claim 1, characterized in that: In step S3, the electrostatic voltage of the electrospinning is 20-30 kV, and the spinning speed of the electrospinning is 0.8-1.3 mL / h; The electrospinning device is selected from any one of a single-needle type, a multi-needle type, a needle-free type or an electrostatic direct writing type.

7. The method for preparing a flexible ceramic nanofiber membrane according to claim 1, characterized in that: In step S4, the high temperature calcination conditions are: in an air atmosphere, heating to 650-1000° C. at a rate of 1-10° C. / min, and keeping the temperature for 0.5-5 h.

8. A flexible ceramic nanofiber membrane obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The fibers of the flexible ceramic nanofiber membrane are in a candied haws shape, and the interior of the fibers of the flexible ceramic nanofiber membrane is a composite pore structure in which mesopores and macropores coexist.

9. Use of the flexible ceramic nanofiber membrane according to claim 8 in a water-induced power generation device, characterized in that: One end of the flexible nanofiber membrane is immersed in an electrolyte solution to form the water-induced power generation device.

10. The use according to claim 9, characterized in that: The electrolyte solution is selected from water or an inorganic salt aqueous solution; The pH of the electrolyte solution is 0-7.

Citation Information

Patent Citations

  • Method for preparing micro / nano porous ceramic fibers by low-temperature electrostatic spinning

    CN102584211A

  • Electrostatic spinning liquid for silicon dioxide fibers and method for preparing porous silica dioxide fibers by utilizing electrospinning method

    CN107354516A

  • Amorphous porous ceramic nanofiber membrane as well as preparation method and application thereof

    CN113426492A

  • Strontium-doped silicon dioxide nanofiber membrane and preparation method thereof

    CN114592277A

  • Preparation method of flexible alumina-based ceramic fiber thick film

    CN116103843A

Cited By

  • Flexible ceramic nanofiber paper based on linear inorganic molecular chain as well as preparation method and application of flexible ceramic nanofiber paper

    CN122013597A